1980
DOI: 10.1007/bf00499914
|View full text |Cite
|
Sign up to set email alerts
|

Identification of harman in the rat arcuate nucleus

Abstract: This communication describes the presence of 1-methyl-beta-carboline (harman) in the hypophysiotropic area of the hypothalamus which incorporates the arcuate nucleus. Diethyl ether extracts of borate-buffered arcuate homogenates were subjected to silica column chromatography and thin-layer chromatography (TLC). Identification of the beta-carboline was accomplished by use of fluorescent spectrometry, gas chromatography (GC), mass spectrometry (MS) and combined gas chromatography-mass spectrometry (GC-MS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

1981
1981
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(11 citation statements)
references
References 35 publications
1
9
0
1
Order By: Relevance
“…Therefore, a ratio of two [3H]harman-labeled sites per one MAO-A holodimer is more likely. Bosin et al (1989) determined a harman concentration of -2.3 nmol/kg in the whole rat brain, but Shoemaker et al (1980) detected 1.3 pmoi/kg in the rat arcuate nucleus. Thus, harman may represent, in some compartments, a significant endogenous MAO-A inhibitor with physiological relevance, as is possibly tribulin for MAO-B (Glover et al, 1988).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, a ratio of two [3H]harman-labeled sites per one MAO-A holodimer is more likely. Bosin et al (1989) determined a harman concentration of -2.3 nmol/kg in the whole rat brain, but Shoemaker et al (1980) detected 1.3 pmoi/kg in the rat arcuate nucleus. Thus, harman may represent, in some compartments, a significant endogenous MAO-A inhibitor with physiological relevance, as is possibly tribulin for MAO-B (Glover et al, 1988).…”
Section: Discussionmentioning
confidence: 97%
“…Harman ( 1-methyl-/3-carboline; Fig. 1) has been detected in many plants and fungi, as well as being an endogenously occumng biogenic amine in rats and humans (Shoemaker et al, 1980;Airaksinen and Kari, 1 9 8 1~;Rommelspacher and Susilo, 1985;Bosin et al, 1989). Harman belongs to a group of naturally occurring B-carbolines (BCs) with neurotropic effects in rat and humans, e.g., tremor, tonic-clonic convulsions, and hallucinations (Gunn, 1935;Sigg et al, 1964;Naranjo, 1979;Airaksinen and Kari, 1981b).…”
mentioning
confidence: 99%
“…As harmane has been identified in both rat brain (Shoemaker et aL, 1980) and human platelets (Bidder et al,, 1979), its MAO inhibitory ability may well have some physiological role; perhaps we would be unwise to ignore it as a possible aetiological agent during studies of abnormal platelet MAO activity . Harmane is also of interest as a possible endogenous benzodiazepine ligand, with an I50 of about 7 x 10 .6 M (Rommelspacher et al, 1980 a).…”
Section: Resultsmentioning
confidence: 97%
“…Rommelspacher et al (1980 b) also reported the presence of the unsaturated carboline, harmane, in the same samples. Harmane has been identified in human platelets (Bidder et al, 1979) and rat arcuate nucleus (Shoemaker et aL, 1980). Perhaps of greater potential interest, Braestrup et al (1980) have reported the isolation of ethyl /?-carboline-3-carboxylic acid, a potent benzodiazepine receptor ligand, from human urine; but, as the authors acknowledge, it seems likely that an unknown precursor became esterified and perhaps further modified chemically, by the extraction procedure.…”
Section: Introductionmentioning
confidence: 96%
“…In addition, harmane has also been shown to interact with I-BS with a higher affinity (IC 50 at I 1 -BS=31 nM, K i at I 2 -BS=49 nM) [97] compared to agmatine. The natural occurrence of harmane in the arcuate nucleus [98], a region rich in both I 2 -BS [99] and MAOs [100], could suggest a possible role for harmane as an endogenous ligand at these sites.…”
Section: Harmane -The Endogenous Ligand At Imidazoline Binding Sites?mentioning
confidence: 99%